Situated harmful traditional practices in South-western Nigeria: recent Progress, challenges and lessons for policy engagements (2023)
The study examined critical discourse on teachers and students' technology appropriation for classroom engagements (TACE). The study employed descriptive research design while population comprised all public teachers and students in Akinyele Local Government Area of Oyo State, Nigeria. Purposive sampling technique was used to select the participants (300 Students and 60 Teachers) from schools with constant supply of computing facilities. Four scales titled Awareness of TACE (r= 0.98), knowledge of TACE (r= 0.71), perception TACE (r= 0.73), and readiness TACE (r= 0.85) were used in data collection. It was discovered that both the teachers and students were aware of technology/digital tools for classroom engagement, but teachers were not deploying the equipments provided and other online tools. Both had average knowledge of TACE. It was further found that the students were ready for the experience but curtailed by teacher factors and other logistics beyond their capacity. Both the teachers and students had positive perception of technology appropriation for classroom engagements. Result also showed that while students are ready for TACE, teachers are not completely ready. It is recommended that teachers should be encouraged to appropriate teaching and learning technologies for classroom engagement